A Study of Location and Utilisation of Health Facilities in Irewole Local Government Area,Oyo State. - Adeyinka, Samson Ajibola (Obafemi Awolowo University, 2014)
This study examines the location and utilization of health facilities in Irewole Local Government area of Oyo State.